Analysis of Students’ Sports Talent: The Correlation between Achievement Motivation and Self-efficacy of Elementary School Students - Matsuri, Matsuri; Chumdari, Chumdari; Adi, Fadhil Purnama; Atmojo, Idam Ragil Widianto; Saputri, Dwi Yuniasih; Ardiansyah, Roy (Mimbar Sekolah Dasar, 2023)
This study aimed to describe: (1) achievement motivation, (2) self-efficacy, (3) student talent, (4) the correlation of achievement motivation with student talent (5) the correlation of self-efficacy with student talent, (6) the correlation of achievement motivation and self-efficacy with students' talents. This study used a quantitative approach with a descriptive method of correlation. While the population of this study was elementary school students in the Former Residency of Solo. The sampling technique was proportional stratified random sampling. The instrument used was a Likert scale model. Data were analyzed using simple linear regression and multiple regression. The results of the study showed that: (1) In general, the description of achievement motivation and self-efficacy of elementary school students in the Former Residency of Solo belonged to the high category; (2) There was a negative and significant relationship between self-efficacy and the talents of elementary school students in the Former Residency of Solo; (3) There was a significant relationship between achievement motivation and self-efficacy with the talent of elementary school students in the Former Residency of Solo simultaneously.